Performance analysis of a multi-carrier CDMA wireless communication system with channel impairment - Rana, Jobayer Anam; nishi, Rahman (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.